2018
DOI: 10.1111/ede.12250
|View full text |Cite
|
Sign up to set email alerts
|

Early limb patterning in the direct‐developing salamander Plethodon cinereus revealed by sox9 and col2a1

Abstract: Direct-developing amphibians form limbs during early embryonic stages, as opposed to the later, often postembryonic limb formation of metamorphosing species. Limb patterning is dramatically altered in direct-developing frogs, but little attention has been given to direct-developing salamanders. We use expression patterns of two genes, sox9 and col2a1, to assess skeletal patterning during embryonic limb development in the direct-developing salamander Plethodon cinereus. Limb patterning in P. cinereus partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…These findings support independent molecular control of digit specification and differentiation and hint at the wide diversity in ontogenetic and heterochronic shifts that have occurred in the limb during urodele evolution (Blanco and Alberch, 1992; Franssen et al, 2005). Similarly, Sox9 expression shows spatiotemporal variability across urodeles (Kerney et al, 2018) and this underscores the need for more comparative limb studies to better understand the ancestral condition. While preaxial vs. postaxial dominance of skeletal formation clearly separates urodele limb development from anurans and amniotes, it is likely this difference points to alterations in the upstream genetic control of digit specification involving Fgfs , Bmps , and retinoic acid (Montero et al, 2017; ten Berge et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These findings support independent molecular control of digit specification and differentiation and hint at the wide diversity in ontogenetic and heterochronic shifts that have occurred in the limb during urodele evolution (Blanco and Alberch, 1992; Franssen et al, 2005). Similarly, Sox9 expression shows spatiotemporal variability across urodeles (Kerney et al, 2018) and this underscores the need for more comparative limb studies to better understand the ancestral condition. While preaxial vs. postaxial dominance of skeletal formation clearly separates urodele limb development from anurans and amniotes, it is likely this difference points to alterations in the upstream genetic control of digit specification involving Fgfs , Bmps , and retinoic acid (Montero et al, 2017; ten Berge et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In amphibians, developmental mechanisms underlying the loss or reduction of traits may be inherently tied to metamorphosis (Eigenmann & Denny, 1900); it has been suggested that pre‐metamorphic stages are more fixed than late labile stages, and that postmetamorphic changes in gene expression or timing serve to compartmentalize trait evolution and loss (Moran, 1994; Wilkens, 2007). Given that toad development is prolonged overall (Fabrezi & Goldberg, 2009; Hetherington, 1987; Smirnov, 1989; Womack, Stynoski, et al, 2018), postmetamorphic truncation of the columella could have resulted from desynchronization of gene regulatory networks for endochondral chondrification and ossification such as runx2, col2a1 , and sox9 (Chapman, 2011; Gómez‐Picos & Eames, 2015; Kerney et al, 2018; Sienknecht, 2013), and/or release of thyroid hormone, which stimulates both metamorphosis and skeletogenesis in anurans (Bassett & Williams, 2016; Hanken et al, 1989). The reversal of postmetamorphic degeneration via resynchronization could explain the inferred regain of tympanic middle ear structures in at least two bufonid lineages, including within Atelopus (Lande, 1978; Pereyra et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Apparently Bmp activity, even when down-modulated, is in excess during limb skeletal element formation and suffices for mesenchymal condensation following cell-cycle exit, but the timing of cell-cycle slowing in anterior relative to posterior limb bud (Figure 5B) determines when cells become permissive to Bmp response and sets the polarity of limb axis formation. Notably, even direct-developing salamanders with a ''paddle'' handplate stage, have a comparatively narrow shaped limb bud, 32 suggesting a lower degree of proliferative expansion. Bmps have recently been implicated in directly regulating cell cycle in the limb, 33 but our results indicate a more direct effect of Gli3 on cell-cycle gene expression.…”
Section: Articlementioning
confidence: 99%